Development of a new performance criteria for higher wire-electrical discharge machining performance considering the ecological and economical aspects / Ibrahem Maher Abdelrahem Soltan - Ibrahem Maher, Abdelrahem Soltan (2016)

(untitled)
Wire electrical discharge machining (WEDM) is a manufacturing process whereby a desired shape is obtained using electrical discharges (sparks). WEDM involves high cutting rates and superior quality to improve machining performance in manufacturing hard materials. The machining performance of computer-controlled WEDM is directly dependent on spark energy (pulse on time, peak current, and gap voltage), pulse frequency (pulse off time and pulse on time), and wire electrode parameters (material, wire speed, and wire tension). In the field of wire electrical discharge machining, it is necessary to develop suitable WEDM technology to facilitate the production of high quality workpiece surfaces at high cutting rates. Surface roughness and white layer thickness are the most important factors in evaluating WEDM surface quality. In order to ensure good surface quality, the surface roughness must be low and the white layer must be as thin as possible, homogeneous, crack-free, and well-bonded to the substrate material. In this study, the effect of cutting parameters is investigated on the machining performance parameters including cutting speed, surface roughness, wire rupture, and white layer thickness. The adaptive Neuro-Fuzzy Inference System (ANFIS) along with the Taguchi method is applied to determine the effects of the significant parameters on WEDM performance. Moreover, a new performance index is proposed to identify the effects of spark energy and pulse frequency simultaneously on machining performance and to identify the wire rupture limit. However, the performance index cannot be used to identify the most feasible wire electrode from ecological (energy and wire consumption) and economic (machining costs) perspectives. Therefore, a new performance criterion (production economic index) is developed to select the most feasible wire electrode considering the economic and ecological aspects along with the performance index to achieve superior machining performance at the lowest cost. This can be done by dividing the performance index by the total machining cost ((Es×DF)/Ct). In addition, a new coated-wire electrode iv design with higher strength for less wire rupture and high machining performance in WEDM is proposed. The results obtained represent a technological knowledge base for the selection of optimal machining conditions along with suitable types of wire electrodes for WEDM in terms of ecological and economic aspects. By applying the proposed performance criterion (Es×DF/Ct), it appears that using lower spark and higher pulse cycle settings with a brass wire electrode can decrease the surface roughness and white layer thickness, and facilitate more economical cutting speed. This could lead to faster cutting with good surface finish and less wire rupture.